2018
DOI: 10.1016/j.palaeo.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

The late Pliocene palaeoenvironments and palaeoclimates of the western Iberian Atlantic margin from the Rio Maior flora

Abstract: Using a revised chronology, a new palynological study on the late Pliocene (Piacenzian and earliest Gelasian) Rio Maior site of the Tagus Basin in western Portugal has been undertaken from the F98 core. Combining light microscopy and scanning electron microscopy, a total of 127 different pollen and spore taxa have been identified from the Piacenzian Lake and indicate the presence of a subtropical to warm-temperate mixed forest during the majority of the Piacenzian (3.6-2.8 Ma). It is only in the latest Piacenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 62 publications
(106 reference statements)
0
6
0
Order By: Relevance
“…Cosmogenic (burial isochron) dating was also used to date the UBS13 unit in the Alvalade Cenozoic Basin, namely at Vila Nova de Mil Fontes (~4 Ma;Ressurreição, 2018) and Sagres promontory (~1.8 Ma; Figueiredo, 2014). Palynological studies also indicated a latest Zanclean to Gelasian age for the aggradation interval of UBS13 (Diniz, 1984;Vieira, 2009, Vieira et al, 2018.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Cosmogenic (burial isochron) dating was also used to date the UBS13 unit in the Alvalade Cenozoic Basin, namely at Vila Nova de Mil Fontes (~4 Ma;Ressurreição, 2018) and Sagres promontory (~1.8 Ma; Figueiredo, 2014). Palynological studies also indicated a latest Zanclean to Gelasian age for the aggradation interval of UBS13 (Diniz, 1984;Vieira, 2009, Vieira et al, 2018.…”
Section: Introductionmentioning
confidence: 94%
“…According to the records of fossil pollen content of the UBS13 sedimentary succession (Diniz, 1984(Diniz, , 2003Vieira, 2009, Vieira et al, 2018Pais et al, 2010;Diniz et al, 2016), a hot and wet climate prevailed during the latest Zanclean and the Piacenzian, with little seasonal contrast and precipitation probably in excess of 1000 mm per year in the less hot seasons. The pollen content in the upper part of the succession records a transition to a less forested environment and cooler climate during the Gelasian.…”
Section: Geological Settingmentioning
confidence: 99%
“…However, these forests progressively lost thermophilous and humid‐loving elements in response to continued cooling and decreasing availability of growing season moisture (Donders et al., 2009; Martinetto et al., 2017). The youngest of these “warm‐wet” floras are reported from the Plio‐Pleistocene of Italy (Martinetto et al., 2017) and Pliocene of Portugal (Vieira et al., 2018) and suggest a southwards contraction in their European distribution during the late Miocene to points of refugia proximal to the coasts (Vieira et al., 2018).…”
Section: Terrestrial Biota and Ecosystemsmentioning
confidence: 99%
“…The botanical assignments of were first updated following Utescher and Mosbrugger (2010), Stuchlik et al (2001;2002; Author accepted version of manuscript accepted in Palynology: https://doi.org/10.1080/01916122.2021.1916636 4 2009; 2014) and Pound and Salzmann (2017). Although it has faced some criticism, the CA continues to be widely used largely due to its simplicity of the technique and consistency of reconstructions from it (Utescher et al 2014;Vieira et al 2018). The reconstructed palaeoclimate of Trwyn y Parc was then compared to CA reconstructions of Germany (Mosbrugger et al 2005) and other northwest European sites (Pound et al 2012b;Burls et al 2021).…”
Section: Methodsmentioning
confidence: 99%